Nephrogenic Ascites in End-Stage Renal Disease Patients Undergoing Hemodyalisis: Case Series - Mulia, Deddy Primadona; Irawan, Rico; Kartika, Herleni; Wangsa, Syahpri Putra; Akbar, Kgs. M. Yusuf Arief; Effendi, Ian; Suhaimi, Novadian; Slamet, Suprapti; Ali, Zulkhair (PERNEFRI (PERHIMPUNAN NEFROLOGI INDONESIA), 2024)
Ascites occurring in individuals with chronic kidney disease (CKD) undergoing hemodialysis (HD) are referred to as nephrogenic ascites (NA). The pathogenesis of NA remains uncertain but involves many interrelated factors. These factors include inadequate dialysis, low ultrafiltration, poor nutrition, increased peritoneal membrane permeability, and impaired peritoneal lymphatic reabsorption. Frequent accompanying complaints are leg edema, nausea, decreased appetite, weakness, and complaints due to hypotension during HD. NA generally carries a poor long-term prognosis, likewise, with complex therapeutic options, both medical and surgical. Management of NA includes education regarding fluid restrictions, a high protein diet, intensive HD, as well as therapeutic modalities with continuous ambulatory peritoneal dialysis (CAPD) and kidney transplantation. CAPD has been proven to improve quality of life and recovery from ascites. The NA in this case report was all related to the patient's low level of compliance against fluid intake restrictions, particularly while experiencing oliguria or anuria. In this case, intensive education regarding limiting fluid intake and high-protein nutrition seems essential for better patient outcomes. On the other hand, the presence of infectious complications gives poor outcomes. Two patients presented with umbilical hernia, which could be an obstacle for CAPD.